Problematika Implementasi Pembelajaran Digital di Sekolah Dasar - Dzuriansyah, Desma; Permatasari, Suci; Dewi, Tira Sari; Suhartono, Suhartono (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Education is the spearhead in building a better future. Through education, it is hoped that the quality of human resources can be improved, character building can be enhanced, and the nation can be advanced, so that it is able to compete in the global arena. The development of technology in this era of globalization is very rapid because human needs are also increasing. The use of technology in education can be seen in the facilities and infrastructure used in learning, learning systems, learning resources, learning methods used, education management systems, and assessment results. However, in its implementation, digital-based learning still faces challenges in terms of teachers, students, and facilities and infrastructure. This study uses a qualitative approach through a literature review method. The purpose of this method is to conduct an in-depth analysis of various scientific literature related to the challenges of implementing digital learning in elementary schools. The data sources consist of national and international scientific journals, academic reference books, policy documents, and relevant research reports. Data collection techniques were conducted through systematic searches using online databases. The research findings indicate that digital-based learning has a positive impact in terms of broad access to information; however, its implementation faces several challenges in education, such as: technological access gaps; digital divides; teacher readiness; and low digital literacy and digital competencies. Solutions that can be implemented include providing equitable access to technology, improving digital literacy, involving parents in supervision, limiting technology in a healthy manner, and providing digital security education for students, teachers, and parents.Pendidikan adalah kunci untuk masa depan yang lebih baik, meningkatkan kualitasbsumber daya manusia, dan karakter bangsa. Teknologi berperan penting dalam pendidikan, tetapi masih ada problematika dalam penerapan pembelajaran digital terkait guru, siswa, dan fasilitas. Penelitian ini menggunakan pendekatan kualitatif melalui metode studi literatur. Tujuan dari metode ini adalah untuk mengkaji secara mendalam berbagai literatur ilmiah yang berkaitan dengan problematika implementasi pembelajaran digital di Sekolah Dasar. Sumber data terdiri dari jurnal ilmiah nasional dan internasional, buku referensi akademik, dokumen kebijakan, dan laporan penelitian yang relevan. Teknik pengumpulan data dilakukan melalui penelusuran sistematis menggunakan pendekatan yang digunakan untuk mengumpulkan, menganalisis, dan menyintesis literatur atau sumber yang relevan lainnya. Kriteria subjek dalam penelitian ini fokusnya adalah guru yang mengalami problematika dalam menerapkan pembelajaran digital di SD. Hasil penelitian menunjukkan bahwa pembelajaran berbasis digital memberikan dampak positif dalam hal akses informasi yang luas, namun dalam penerapannya terdapat beberapa problematika yang menjadi tantangan dalam pendidikan seperti: kesenjangan akses teknologi; kesenjangan digital; kesiapan guru, serta rendahnya literasi digital dan kompetensi digital. Solusi yang dapat diterapkan meliputi penyediaan akses teknologi yang merata, peningkatan literasi digital, keterlibatan orang tua dalam pengawasan, pembatasan teknologi secara sehat, serta edukasi keamanan digital untuk siswa, guru, dan orang tua.